IMPLEMENTASI PRINSIP EKONOMI SYARIAH DALAM PENGELOLAAN ENJE MART DI PONDOK PESANTREN NURUL JADID - Alief Hidayatullah, Muhammad; Helmy Rozaly, Muhammad (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, IAIN Fattahul Muluk Papua, 2025)
This study aims to deeply examine the implementation of Sharia economic principles in managing Enje Mart, located at Nurul Jadid Islamic Boarding School. Sharia economic principles, including values of justice, transparency, sustainability, and prohibition of riba, serve as the primary foundation for conducting Enje Mart's operational activities. The research adopts a qualitative approach with a case study method to provide a comprehensive depiction of how Sharia values are applied. Data collection techniques involve in-depth interviews with managers, direct field observations, and analysis of supporting documents. The results reveal that Enje Mart has successfully implemented sharia principles in various aspects, such as financial management based on profit-sharing systems, procurement of goods from local business partners, and service approaches emphasizing Islamic ethics. Additionally, a technology-driven stock management system is utilized to ensure efficiency and honesty. However, the study also identifies challenges, including limited human resource capacity in understanding the details of sharia principles and constraints in business capital. To address these challenges, regular training and mentoring were conducted by Sharia economic institutions affiliated with the boarding school. The study concludes that Enje Mart's management reflects an optimal effort in applying sharia economic principles despite facing some obstacles. Its impact is evident not only in the increased income of the boarding school but also in empowering the surrounding community's economy. This study is expected to serve as a strategic reference for other Islamic boarding schools in developing sustainable and blessed sharia-based businesses.